A study on sleep patterns and sleep problems in children aged 6 to 15 years as perceived by their parents - Tharakan, Riya Mary; Shenoy, K. Varadraj (International Journal of Contemporary Pediatrics, 2019)
Background: The objective is to study the sleep pattern and occurrence of sleep problems in children aged 6 to 15 years, visiting the Outpatient clinic at a tertiary care hospital, as perceived by the parents and to establish the common causal association as perceived by the parents for developing sleep problems. Methods: The study design was based on the descriptive study. The duration of the study was from 1st June to 31st July. Data was collected from all the children visiting the Pediatric OPD and those who are admitted, Department of Pediatrics, Father Muller Medical College. Sample size: convenient sampling. Considering the prevalence of sleep disturbance in children as 10%, estimated error of 5% and confidence interval of 5%, sample size was 139. Children who followed the inclusion and exclusion criteria were considered for the study. Informed consent was taken from the parent. Relevant details were asked to the parents of the child and a pre-designed proforma was filled by the investigator accordingly. SDSC questionnaire was used and a cut off score of 39 was considered. Results: Out of the 140 children who completed the survey, 48% of the children had sleep disturbances. The most common was disorder of initiating and maintaining sleep. The most common association was with need for accompaniment, followed by use of gadgets. The prevalence of sleep disorders is underestimated, and it is important to recognize them early. Conclusions: The increasing use of electronic gadgets could be a possible cause of sleep disturbances, which suggests that the exposure of children to these gadgets maybe reduced.